DIET IN GOUT AND HYPERURICEMIA - O. V. Zhelyabina; M. S. Eliseev (Научно-практическая ревматология, 2017)
The paper reviews the most important works devoted to the study of the impact of individual foods and food components on the risk of gout, its clinical manifestations and the level of uricemia. It considers some mechanisms probably underlying the impact of dietary patterns on the level of uricemia. It is shown that the available data on possible alterations in the diet with their proper application can considerably affect both the incidence of gout and the course of the current disease.